Law's history American legal thought and the transatlantic turn to history - Rabban, David M., 1949- (Cambridge historical studies in American law and society, 2013)
"This is a study of the central role of history in late-nineteenth century American legal thought. In the decades following the Civil War, the founding generation of professional legal scholars in the United States drew from the evolutionary social thought that pervaded Western intellectual life on both sides of the Atlantic. Their historical analysis of law as an inductive science rejected deductive theories and supported moderate legal reform, conclusions that challenge conventional accounts of legal formalism. Unprecedented in its coverage and its innovative conclusions about major American legal thinkers from the Civil War to the present, the book combines transatlantic intellectual history, legal history, the history of legal thought, historiography, jurisprudence, constitutional theory and the history of higher education"--